0002 Using Multidisciplinary In Situ Simulation in the Emergency Department to Increase Learning and Highlight Potential Patient Safety Issues. (1st November 2014) - Connolly, Christopher; Swift, Jennie; Hormis, Anil; Stephenson, Daniel
Abstract : Background: Simulation based education has been used in the Rotherham Foundation Trust for the past four years. We have moved some of these sessions from the simulation suite to in situ in the Emergency Department (ED) resuscitation room, to increase learning and highlight potential patient safety issues. Methods: Multidisciplinary teams compromising of ED staff attend sessions lasting 1 to 2 h. These comprise of clinical scenarios of twenty minutes of simulation followed by a debrief lasting approximately forty minutes. Scenarios are based on the College of Emergency Medicine curriculum. A medium fidelity METIman manikin, is used, in the resuscitation room, using the same drugs and protocols that are daily. Sessions are facilitated by senior ED medical and nursing faculty who have expertise in simulation. Following the session a report is compiled under the titles of Systems and environment, Technical and Non- technical Skills. This report is submitted to the ED Quality Governance meeting, so that safety issues identified can be resolved in the same way as issues identified in 'real life' incidents. Results: Analysis of feedback forms to date- quantitative and qualitative feedback has been compiled from delegate feedback along with session summaries compiled by the simulation faculty. Qualitative feedback: "Very useful to do the simulation in resus, and with nursing staff - allowed us to work better as a team and build a better relationship". Excerpts from reports: Discussion around location of advanced airway adjuncts specifically laryngeal masks: staff identified that they didn't know where to locate them. Based on our experiences running the sessions we have compiled a short 'beginners guide' document to be shared amongst other trusts. Impact and expectations: We intend in situ simulation to become an important tool for quality and safety improvement in the ED.